1996
DOI: 10.1002/actp.1996.010470506
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of interpenetrating networks from acrylates of d‐block elements

Abstract: Systematic synthesis of interpenetrating polymer networks (IPN) from poly(chromium acrylate) (PCrA) and zinc acrylate (ZnA) using divinyl benzene (DVB) as crosslinker has been carried out. Swelling studies and scanning electron microscopy (SEM) were performed to examine the extent of crosslinking and phase behavior of the IPN. The crosslinking decreases with the increase of linear polymer concentration and its molecular weight, respectively. On the other hand, it increases with the increase of concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…None of the blends exhibited a continuous uniform phase, which proves that the interaction between LDPE-g-MA and TPS was weak. In other studies [32], blends of starch, LDPE, and LDPE-g-MA were prepared. It was observed that the use of LDPE-g-MA played an important role in promoting interfacial adhesion between the TPS and LDPE.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
“…None of the blends exhibited a continuous uniform phase, which proves that the interaction between LDPE-g-MA and TPS was weak. In other studies [32], blends of starch, LDPE, and LDPE-g-MA were prepared. It was observed that the use of LDPE-g-MA played an important role in promoting interfacial adhesion between the TPS and LDPE.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%